Impacts of Stressful Life Events and Traumatic Experiences on Onset of Obsessive-Compulsive Disorder - Murayama, Keitaro; Nakao, Tomohiro; Ohno, Aikana; Tsuruta, Sae; Tomiyama, Hirofumi; Hasuzawa, Suguru; Mizobe, Taro; Kato, Kenta; Kanba, Shigenobu (Frontiers in Psychiatry, 2020)
Not a few patients with obsessive-compulsive disorder (OCD) have experienced events that affected the onset. The onset of OCD is not limited to the original meaning of trauma; rather, traumatic experiences such as unexpected exposure to contaminants or various stressful life events often cause the onset of OCD. It would be useful to understand the experiences surrounding the onset, including stressful life events and traumatic experiences, for comprehension of the pathophysiology of OCD. In the present study, we investigated the onset conditions of 281 patients with OCD and compared clinical characteristics among groups with or without stressful life events including traumatic experiences. As a result, 172 (61.2%) participants had experienced various stressful life events, and 98 (34%) participants had had traumatic experiences before the onset. Further, the participants who had had stressful life events showed more contamination/fear symptoms compared to those without such life events. Meanwhile, the patients who had had specific traumatic experiences showed a tendency toward hoarding obsessions. To comprehend the pathophysiology of OCD, it is important to understand the stressful life events that precede its onset.